Environmental and resource management plan for the proposed Tun Mustapha Park (TMP), Sabah, Malaysia - Robecca Jumin (2015)
The proposed Tun Mustapha Park (TMP) is located in the northern region of Sabah, Malaysia. The intention to gazette TMP was approved by the Sabah State Government in March 2003 with three management goals: i) to conserve marine biodiversity; ii) to enable sustainable development; and iii) to alleviate poverty of coastal villagers. The ecosystem approach used in the management of the proposed TMP will require the development of an integrated management plan that will be able to fulfill multiple management objectives. The process to design the zoning plan for the proposed TMP forms the basis of this Ph.D. study. The overall aim of this study is to assess the conservation planning process and the use of numerical optimization tool to achieve two Marine Protected Area (MPA) objectives, i.e. biodiversity conservation and fisheries management objectives, in a stakeholder driven MPA design process. This is achieved through four main group of work: i) analysis and synthesis of data from a community survey conducted in 2006-2007; ii) identify and map key habitats that form the key conservation features of- TMP through review and verification of existing information; iii) analyse and synthesise fisheries data to establish status of fisheries, management isues and important fishing areas, and iv) design and develop draft zoning plan for the proposed TMP. The design process combined both use of systematic conservation planning tool, Marxan with Zones, and stakeholder consultation to design and revise the draft zoning plan. A suite of biophysical and socioeconomic decision principles were developed by multiple stakeholders in order to help address the more general management goals of TMP. Where possible, these goals were used to guide the Marxan with Zones analysis, to identify priority areas for four different zones: i) Preservation, ii) Community-use, iii) Multiple-use, and iv) Commercial fishing. Two main types of data were collected from scientific surveys and local knowledge and used in Marxan with Zones: i) conservation features, including habitat and species data; and ii) cost features, including the location of villages and fishing effort. TMP was divided into four regions to address the biophysical design principles, and a target of at least 30% of each habitat in each region was represented in the preservation zone. Fishing is an important component of TMP. A large number of its communities depend on coastal fisheries for their subsistence and small scale operation for livelihood. Impacts on the fishing community of TMP were minimized through maintenance of access to fishing grounds. A target of at least 70% of small scale fishermen’s fishing grounds (within 3 nautical miles from the shore) in either Community Use (CU) or Multiple Use (MU) zones was set to ensure that traditional and non-destructive fishing practices could continue. The output of this process is a draft zoning plan for TMP that was used in the consultation process for stakeholder input into the designing process.